Microstructure and flexural strength of hafnium diboride via flash and conventional spark plasma sintering. Issue 4 (April 2019) - Demirskyi, D.; Suzuki, T.S.; Grasso, S.; Vasylkiv, O.
Abstract: Microstructure evolution in bulk hafnium diboride ceramics prepared by spark plasma sintering in flash regime was compared with conventional spark plasma sintering. The conventional and flash spark plasma sintering resulted in ceramics with a high relative density exceeding 96% of their theoretical density. A remarkably fine grain size distribution was noticed for the specimen prepared in the flash regime. This atypical microstructure evolution provides a possible insight into the mechanism of flash sintering for conductive bulks. The room temperature flexural strength of the hafnium diboride processed by flash SPS was 650 MPa which is 140 MPa higher than the sample produced by conventional SPS.